Understanding the Reporting of Intangibles from a Business Perspective - Fischer, Thomas; Baumgartner, Kim (Intangibles in the World of Transfer Pricing, 2021)
In the knowledge-based economy, the intangibles of firms have become the most important strategic resources and key drivers of firm value and business success. Traditional financial disclosures are no longer sufficient to convey a firm’s wealth-creation potential to stakeholders. Instead, intellectual capital reports have gained increasing importance to ensure transparency and reduce information asymmetries. Tax departments rely on these reports as a starting point for the identification and valuation of intangibles that are relevant for the transfer pricing process. This chapter provides a comprehensive overview of a firm’s opportunities for reporting intangibles internally and externally. It also includes a description of suitable tools for internal reporting, such as an intellectual capital statement, and explains the German reporting regulations for intangibles as well as further approaches to voluntary external disclosure of intangible value
Keywords: Intangibles; Reporting; Disclosure; Intellectual capital statement; Integrated reporting